Coordinated control for distributed generation in microgrids - Xu, Xin (Nanyang Technological University, 2021)
Distributed generation system based on microgrid technology is an essential approach to develop renewable energy, improve the reliability of the power supply and expand the supply capacity of the power system. The power supply of distributed grid can be formed by a variety of energy resources through power transformation, and these power supply units are decentralized and are connected to the grid. The power supply unit of the microgrid based on distributed generation is generally the power supply with power electronic converters. The power converter is the core of the whole distributed generation system, which is responsible for converting distributed energy into electric power and realizing the grid-connection of the distributed generator.